Efektifitas Doa Islami Terhadap Frekuensi Nadi, Frekuensi Nafas, Tekanan Darah, Saturasi Oksigen Pada Pasien Congestive Heart Failure - Kasron Kasron; Susilawati Susilawati; Wishnu Subroto (STIKes MERCUBAKTIJAYA, 2023)
Congestive Heart Failure (CHF) is a disease that has symptoms of shortness of breath, changes in oxygensaturation vital signs and causes sleep disturbances. Praying is an action that has multifunctions. It ishoped that the act of praying can have a positive effect on CHF patients. The aim of the research was todetermine the effect of Islamic prayer on pulse frequency, respiratory frequency, blood pressure andoxygen saturation. The research was conducted using a quasi-experimental approach in August –September 2022. The sampling method used purposive sampling, with 30 CHF patients in the interventiongroup and 30 in the control group. Prayers are given for 3 days. Analysis uses the Wilcoxon test and MannWhitney test. The results of the study showed that after the intervention the average pulse rate in theintervention group was 87.6 ± 1.1, respiratory frequency 24.6 ± 1.2, systolic blood pressure 113.1 ± 5.2and oxygen saturation 93.4 ± 1.2, and showed that there were no significant differences in the interventiongroup before and after the intervention in pulse frequency (pv: 0.675), respiratory frequency (pv: 0.765),systolic blood pressure (pv: 0.362) and oxygen saturation (pv: 0.886). The conclusion of the research isthat there is no effect of providing prayer guidance on pulse frequency, respiratory frequency, bloodpressure, oxygen saturation in CHF patients. The suggestion for this research is to continue the researchby increasing the number of research respondents